2019
DOI: 10.1002/jat.3912
|View full text |Cite
|
Sign up to set email alerts
|

The glycolytic shift was involved in CdTe/ZnS quantum dots inducing microglial activation mediated through the mTOR signaling pathway

Abstract: The excellent optical property and relatively low toxicity of CdTe/ZnS core/shell quantum dots (QDs) make them an advanced fluorescent probe in the application of biomedicines, particularly in neuroscience. Thus, it is important to evaluate the biosafety of CdTe/ZnS QDs on the central nervous system (CNS). Our previous studies have suggested that the high possibility of CdTe/ZnS QDs being transported into the brain across the blood‐brain barrier resulted in microglial activation and a shift of glycometabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…17,18 The physicochemical properties of CdTe QDs and CdTe@ZnS QDs were evaluated as the method described in a previous study. 12 All characteristic data of QDs are presented in Table S1 and Figure S1.…”
Section: Preparation and Characterization Of Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 The physicochemical properties of CdTe QDs and CdTe@ZnS QDs were evaluated as the method described in a previous study. 12 All characteristic data of QDs are presented in Table S1 and Figure S1.…”
Section: Preparation and Characterization Of Qdsmentioning
confidence: 99%
“…Although our research group has shown the roles of sizes and surface coatings influencing the neuroinflammatory reactions to CdTe QDs in neuronal cells, 12,13 the neuroinflammation-promoting effects of CdTe QDs in in vivo biological models are still not clear. In this study, two animal models, ie, Caenorhabditis elegans and Institute of Cancer Research (ICR) mice, were used.…”
Section: Introductionmentioning
confidence: 97%
“…Upon infection, injury or stress, microglia migrate to the site of inflammation, assume an amoeboid shape and secrete cytokines, chemokines and ROS ( 88 ). Metabolic changes in neurons and glial cells upon injury or stress (e.g., lactate, succinate and citric acid) are important in the formation of synaptic plasticity in pain sensitization and neuropathic pain, as well as a variety of other central nervous system diseases ( 89 ).…”
Section: Effects Of Glycometabolism Reprogramming On Synaptic Plasticitymentioning
confidence: 99%
“…86 Wu and colleagues found that when CdTe/ZnS QDs were injected into the tail vein of mice to observe the activation of hippocampal microglia, the microglia were transformed into M1 and M2 phenotypes, resulting in neuron damage. 87 Caenorhabditis elegans has emerged as a biological model for the study of neurotoxicity in vivo due to its strong reproductive capacity, transparent body, simple neural structure and low cost. CdTe quantum dots have been reported to cause damage to the nervous system of C. elegans .…”
Section: Cytotoxicity Of Quantum Dotsmentioning
confidence: 99%